The effect of Cu loading on Ni/carbon nanotubes catalysts for hydrodeoxygenation of guaiacol. Issue 32 (11th March 2016) - Dongil, A. B.; Bachiller-Baeza, B.; Rodríguez-Ramos, I.; Fierro, J. L. G.; Escalona, N.
Abstract : Commercial carbon nanotubes (CNT), were used as supports to prepare Ni/CNT catalysts with a 15 wt% Ni loading and NiCu x /CNT catalysts with Cu loadings of x : 1.5, 2.25, 3.0 and 3.75 wt% were prepared. Abstract : Commercial carbon nanotubes (CNT), were used as supports to prepare Ni/CNT catalysts with a 15 wt% Ni loading and NiCu x /CNT catalysts with Cu loadings of x : 1.5, 2.25, 3.0 and 3.75 wt% were prepared. The catalysts were characterized by N2 physisorption, H2 -temperature programmed reduction (TPR), transmission electron microscopy (TEM), STEM-HAADF and X-ray photoelectron spectra (XPS), and they were evaluated in the conversion of guaiacol at 573 K and 5 MPa H2 pressure for 4 h in a batch reactor. The characterization showed that Ni–Cu alloys were formed which existed along with Ni, Cu and NiO entities. The Ni metallic particle size was lower upon increasing Cu content, however the increased proportion of NiO species and the coverage of Ni sites with Cu diminished the intrinsic activity. The addition of Cu also decreased the hydrogenolysis and deoxygenation ability for the catalysts up to 3 wt% of Cu, which can be related to the lower size of Ni ensembles. Beyond that percentage, the selectivity was modified and it was attributed to changes in the Ni dispersion.